(untitled) (Research, Society and Development, 2022)
As an early detection strategy, the ASSIST test (Alcohol, Smoking and Substance Involvement Screening Test) was created, where health professionals can promote the diagnosis of risk associated with drug use and propose interventions. However, the low training offered to health professionals to apply the test requires the gathering of information that can provide subsidies that facilitate the work routine of these professionals. The purpose of this article To evaluate the knowledge and use of the ASSIST test by health professionals and its importance in Primary Health Care in Brazil. This is an Integrative Literature Review carried out in PubMed, SciELO, LILACS, SCOPUS and MEDLINE databases. As inclusion criteria, studies published in the period between 2012 and 2022 were used, complete publications with texts in Portuguese and English published in Brazil and whose theme included questions involving the ASSIST screening test. A cross between “alcohol and health professional” was performed, shortly after a new cross was performed, within these results, using “alcohol and health professional and ASSIST”. In this way, the final quantity consisted of 20 articles produced. The results found and discussed above suggest the need to rethink the applicability of ASSIST as a mandatory protocol. Therefore, it is necessary to understand the importance of prioritizing a routine focused on preventive care withc a fous on results, allowing everyone to be involved and thus contributing to the improvement of the patient’s well-being.